The influence of perceptual and cognitive factors in the development of food preferences - Pybis, Joanne (2011)
Despite a considerable amount of research investigating factors that influence the development of food preferences, there is very little research considering factors associated with food items themselves and the cognitive processes used by children to determine acceptance or rejection of a novel food. When offered a new food, children will see what colour, size and shape it is and may be able to determine its texture. In addition, they will be able to smell the food and may even be informed of what the food is called by their parents labelling it. Hence children will have a significant amount of knowledge of what the food they are being offered is like. It may therefore be reasonable to suggest children will use this knowledge and make comparisons to prior experience with 'similar' foods. This thesis presents three experimental chapters which aim to explore the role of perceptual (e.g. colour, texture and size) and cognitive (categorisation) factors on the development of food preferences. Chapter 2 presents an Explicit Preference Task, which enables children to self-report on their food preferences, complemented by parental report Food Preference and Frequency questionnaires. Chapter 3 presents a Longitudinal Food Diary method exploring the relationship between preference and exposure. Finally in Chapter 4 using a series of match-to-sample experiments to consider if children use colour as a basis for categorisation of food objects, a comparison is made against non-food objects. Results indicated children to dislike food colours particularly associated with vegetables more so than other food colours. This was found to be related to the amount of exposure they had to those foods and specifically results indicated children to use food colour as a basis for rejection of novel foods. It was also observed that whilst children use shape as a basis for categorisation of non-food objects, they are more inclined to categorise foods on the basis of colour.